Implementasi Sistem Pengarsipan Dokumen Menggunakan Metode Spiral Berdasarkan Hasil Evaluasi Lean Six Sigma - Bobi Agustian (Teknik Informatika Universitas Pamulang, 2016)
Filing is the one of important process which happen in organization. Filing as a purpose to keep any important document manner with structural, orderly and safe. So if the document is consuct then easy to search and get that document. Most of organization in filing still use the manual process. Filing document still using many papper and storage media in case. This process is containing many risk. Such as damage, lost, document disorder. So that caused difficult to get document back. Old method also cause many cost. And if the document increase so much, then the system document filing is needed to help in document archieve and reduce cost. This thesis describes the development of a filing system using a spiral system development method based on the results of the evaluation study using lean six sigma method. System development using the spiral method consists of six processes, ie processes with user communications, process planning, process risk analysis, process design, implementation and testing process, and user evaluation process. The assessment is a lean six sigma methods of evaluation are used to detect a process that contains no added value, as well as search for sigma value of a production process. The results of this research can be used to establish a filing system that is able to assist the operational activities of the staff involved in achieving the goal to meet the needs and desires of consumers better, efficient and effective.